A study on team determinant factors that affecting productivity a case study at Tenaga Nasional Berhad, Bandar Melaka / Muhammad Izwan Izham and Muhamad Faris Sohaimi - Izham, Muhammad Izwan; Sohaimi, Muhamad Faris (Faculty of Administrative Science and Policy Studies, 2014)
This research is about team determinant factors affecting productivity at TNB Bandar Melaka. The objectives of this research are to determine the relationship between teamwork, team trust, esprit de corps and productivity. About 132 respondents were selected as sample size of this research. Convenience sampling technique was used when selected the 132 respondents at TNB Bandar Melaka. The respondents were required to answer questionnaires that consists of 40 questions include 5 demographic section. The researcher use Descriptive statistic, Cronbach’s Alpha and Spearman rank Order Correlation to analyze the data gathered using Statistical Package for Social Science (SPSS) Version 20.0. The result indicates that there are positive correlations between team determinant factor and productivity.